(untitled) (Vietnam Journal of Community Medicine, 2022)
Background: Patient safety culture (ATNB) is considered the leading criterion in the treatment and care of patients at medical facilities. Objective: Describe the situation and analyze some factors related to patient safety culture of health workers at Kien Giang general hospital, 2021. Methods: Cross-sectional study, quantitative research. Results: The study collected quantitative information from 950 health workers at Kien Giang general hospital through questionnaires. The research results show that the rate of health workers who respond positively to the patient safety culture is quite high. Conclusion: The rate of positive response to patient safety culture of health workers is 70.1%. The Factors related to patient safety culture: Group of health workers who have contact with patients; The group of health workers are nurses and the group of health workers are doctors/pharmacists (p<0.05).